Improving the Quality of Facilities and Infrastructure through Facilities and Infrastructure Management - Khairani; Annisa, Fella; Zuraira, Tasya; Hasanah , Uswatun; Winanda , Arya (Yayasan Pendidikan Islam Akmalia, 2023)
The purpose of this research article is to find out the relationship between improving the quality of facilities and infrastructure with management facilities and infrastructure as well. The research method used in this study is a qualitative approach method with interviews which then the results of the interviews are analyzed. Educational facilities and infrastructure are part of efforts to aspirate educational goals in general and learning objectives in particular to take place effectively and efficiently. The context of management of facilities and infrastructure in the interpretation of the Koran is contained in the interpretation of Surah An-Nahl (16) verses 68-69 which contains the interpretation of the concept of building a division of labor in preparing infrastructure so that it is effective and on target so that its implementation is in accordance with its value in use. strengthened by the hadith of Rasulullah SAW if it is contextualized into the useful life of facilities and infrastructure..